DURINGWORD WAR II SCIENTIFIC RESEARCH OF KOREAN HISTORIANS ON HISTORICAL CHANGES IN TAJIKISTAN - Turdimirzayev Mirjalol Khamidjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores the contributions of Korean historians to the understanding of historical transformations in Tajikistan following World War II. Over the past few decades, a growing number of Korean scholars have directed their academic focus toward Central Asia, particularly Tajikistan, due to shared historical experiences, geopolitical interests, and the expanding scope of Korean area studies. The period after World War II marks a significant era in Tajikistan’s development, encompassing socio-political changes, economic restructuring under Soviet policies, demographic shifts, and cultural transformations. Korean historians have approached these changes through various lenses including comparative history, post-colonial theory, and socio-political analysis. This article provides a comprehensive review of their research outputs, highlighting the methodologies employed, the academic contexts within which these studies emerged, and the key findings about Tajikistan’s post-war trajectory. By evaluating Korean scholarly perspectives, this study sheds light on the transnational academic dialogue and the role of Korean historiography in enriching the global understanding of Central Asian history. The article aims to not only document the historical findings but also analyse the motivations and frameworks that Korean scholars bring to the study of Tajikistan’s post-World War II history.